Оптимизация геометрии очага деформации при прессовании - Шепельский, Н. В.; Свяцкий, В. В.; Shepelskyi, M.; Sviatskyi, V. (ДДМА, 2001)
Рассмотрены вопросы оптимизации профиля матричной воронки на основании анализа поля линий скольжения установившейся стадии прессования через симметричную одноочковую матрицу для получения пресс-изделий с минимальными энергосиловыми параметрами. The questions of matrix funnel structure optimization are considered on the basis of the analysis of a sliding lines field of the established pressing stage through symmetric single-hole matrix for reception of the separated fibres during cast granules pressing.
Optimization of the geometry of the deformation center during pressing
Keywords: прессование; сдвиговые деформации; гранула; профиль матрицы; поле линий скольжения; extrusion; shear deformations; granule; die funnel profile; slip line field